The blue planet seas of life - Fothergill, Alastair; Holmes, Martha 1961-; Byatt, Andrew; Attenborough, David 1926-; Fenton, George (Distributed by BBC Worldwide Americas Distributed by Warner Home Video, 2007)
Explores the world's oceans and is the definitive exploration of the marine world, chronicling the mysteries the deep. Discusses concepts such as evolution, the food chain, survival of the fittest, and the future of that omnipresent non-sea creature known as Man.